Catherine II: Uniform Dresses and Regional Uniforms. (September 2019) - Ivleva, Victoria
Abstract : Soon after the coup d'état of 1762, which brought Catherine II, also known as Catherine the Great, to power, Vigilius Erichsen painted the equestrian portrait of the Empress in the Life Guards' uniform. Catherine wore this uniform during the coup that dethroned her husband, Peter III. This article analyses this episode of cross-dressing in the context of Catherine's legitimation narrative. It further examines the uniform dresses that she wore for various regimental occasions. The dresses combined elements of traditional Russian garments and European fashion. The final section of the article studies the regional uniforms that Catherine II introduced for nobles, civil servants and their wives as part of her regional reforms after Pugachev's rebellion (1773–1775). I discuss these uniforms in the context of a revival of interest in the regions and local civil service, and in the context of national and transnational processes in Europe in the late eighteenth century.